A test of behavioural changes to electronic levy: Evidence from mobile money transactions in a developing country - Carlos Kokuvi Tetteh; Anthony Amoah; Edmund Kwablah; Rexford Kweku Asiama; Godson Ahiabor (Cogent Economics & Finance, 2023)
Even before its introduction, the electronic levy in Ghana stirred up different behavioural reactions from the public, despite the intention to use its proceeds to provide better public services. As a result, this study examines some of these behavioural changes using pre-tax survey data on the proposed electronic levy. Using a sample size of 2,810 individuals with mobile money accounts, we estimate a multivariate logit model with its marginal effects to determine the associated drivers of individuals' behavioural changes to the proposed tax. The results show that the electronic levy is likely to have an immediate impact on an individual's behaviour in positive and negative ways. Thus, while about 88% of the respondents indicated that they are likely to stop using mobile money or reduce their transactions, approximately 12% of the respondents rather reaffirmed their willingness to keep using mobile money or perhaps increase their mobile-money transactions. Furthermore, we find evidence that income, marital status, objective knowledge, trust in government, and the implementation timeframe are the statistically significant determinants of behavioural changes to the electronic tax in Ghana. The results suggest varying behavioural responses to the electronic levy in Ghana, which threaten the realization of expected revenues. We recommend proper education and advocacy at all levels and a keen consideration to implement the levy later, perhaps, when there is more trust in the government's ability to use tax revenues prudently.
Keywords: 330; behavioural changes; electronic levy; electronic tax; mobile money; survey